Influence - Shepard, Sara, 1977-; Buckingham, Lilia (Delacorte Press, 2021)
After her family moves to Los Angeles, Delilah Rollins, already a minor Internet celebrity, plunges into the competitive and glamorous world of social media influencers, but can cosmetics and good lighting conceal cheating, manipulation, blackmail, and murder?